Adoption of electronic procurement in Singapore. - Chia, Boong Kheng. (2008)
The emergence of new Internet technologies has far-reaching ramifications on the way business is conducted. Notably, it has given rise to e-commerce, which is the transaction of business via the Internet. Recognising the importance of the Internet as a powerful business tool, the Singapore government has actively promoted e-commerce. It aims to transform Singapore into an e-commerce hub.